Identification, occurrence, incidence and transmission of phytoplasma associated with Petunia violacea witches' broom in Iran. Issue 10 (23rd July 2019) - Hemmati, Chamran; Nikooei, Mehrnoosh; Bertaccini, Assunta
Abstract: A petunia witches' broom (PvWB) disease, characterized by phyllody, virescence, witches' broom, little leaf and yellowing, was observed in municipal lands and parks in Bandar Abbas, Hormozgan province, Iran. The disease was present with an average incidence of 20%. PCR and sequencing analysis carried out on selected samples from symptomatic plants showed the presence of a phytoplasma associated with the disease. The molecular comparison of the 16S ribosomal gene indicated 99% sequence identity with the one of " Candidatus Phytoplasma australasia". This phytoplasma was transmitted to healthy petunia plants under experimental conditions by the leafhopper Orosius albicinctus that was then demonstrated to be a vector of this phytoplasma.